Bacterioplankton abundance and production in the Western Bransfield Strait in March 2002 - S. A. Seregin (Ukrainian Antarctic Journal, 2003)
Bacterioplankton abundance and production in the 100 m layer was determined during complex investigations in 8 - 17 March 2002 in the region of the Western Bransfield Strait. The mean abundance at the surface was 2,62 105 cell ml-1 (from 1,25 ·105 tо 5,11·105) and mean daily production - 0,75 mg С m-3. A typical pattern of cell abundance and production vertical distribution is their reducing with depth. But at 20-40 m depths local maximum peaks of abundance, associated with picnogradients were often observed. The mean 100-m integrated bacterioplankton production in the region was 57,6 mg Сm-2 d-1. The non-uniformity of bacterial abundance and production horizontal distribution connected with mesoscale structures of different water masses was marked. Epicenter of maximal parameters was fixed in the area between the islands of Liwingston, Snow and Deception. High bacterioplankton abundance in the Gerlache Strait was not followed by productivity growing. Minimal abundances and productions were in the Weddell sea water masses in the center and south-eastern part of the investigated territory.